Modification of Gajah Cassava Starch Originating from East Borneo, Indonesia, using Ozone Oxidation - Murdianto, Wiwit; Anggrahini, Sri; Sutardi; Pranoto, Yudi (Pakistan Journal of Nutrition, 2019)
Background and Objective: Cassava is an abundant, low cost and renewable food source. The Gajah variety of cassava, which originates from East Borneo, Indonesia, has a high potential as a source of starch. Oxidation using ozone is an environmentally friendly technology that is safe and does not generate waste products. Oxidized cassava starch is a raw material for various food products. This research aimed to investigate the oxidation of cassava starch using ozone for different ozonation times and study its properties, including the carbonyl and carboxyl contents, color, swelling power, solubility and pasting ability. Materials and Methods: Gajah cassava starch was obtained from East Borneo, Indonesia. Oxidation of a 10% cassava starch suspension was performed using 2 ppm dissolved ozone, stirring at 300 rpm for 0, 15, 30, 45 and 60 min at 30°C. Results: The data showed that the carbonyl, carboxyl and amylose contents, whiteness index, solubility and starch paste clarity increased with increasing ozonation time and increased from 0.02-0.12%, 0.04-0.14%, 35.76-41.38%, 87.27-92.43%, 34.08-85.56% and 27.62-81.56% respectively. However, the swelling and pasting abilities decreased. Conclusion: It can be concluded that oxidation of Gajah cassava starch using ozone improves its characteristics, increasing its potential as a raw material for many food products.